Perovskite Solar Cells With Modified Carbon Electrode and CuSCN Interlayer Processed Under Ambient Conditions - Junivan Sulistianto; Akinori Konno; Tomy Abuzairi; Nji Raden Poespawati (International Journal of Photoenergy)
Carbon-based perovskite solar cells (PSCs) have the advantages of a long lifetime and are compatible with highly scalable manufacturing processes. The use of carbon electrodes and the absence of a hole selective layer (HSL) promote a simplified fabrication process. However, the efficiency of HSL-free carbon-based PSCs is inferior to PSCs that utilize metal electrodes and HSL due to poor hole extraction at the perovskite/carbon interface. To overcome those issues, researchers added an interlayer on the perovskite/carbon interface or incorporated additive material into the carbon layer. However, there is limited research on utilizing both strategies to improve carbon-based PSC performance. Here, we use CuSCN as an interlayer between the perovskite/carbon interface and a carbon additive in carbon-based PSCs. By utilizing both strategies, the charge transfer of carbon-based PSC was significantly improved compared to carbon-based PSC utilizing only one improvement strategy. Confirmed by photoluminescence (PL) and electrochemical impedance spectroscopy (EIS) characterizations, the CuSCN interlayer and CuSCN-incorporated carbon electrode enable more efficient hole transfer, resulting in an increased power conversion efficiency from 0.58% to 5.06%. The proposed PSC structure shows promising results for further improving carbon-based PSC performance.